High fishing intensity reduces females’ sperm reserve and brood fecundity in a eubrachyuran crab subject to sex- and size-biased harvest - Pardo, Luis M; Riveros, Marcela P; Fuentes, Juan Pablo; Pinochet, Ramona; Cárdenas, Carla; Sainte-Marie, Bernard (ICES journal of marine science, 2017)
Size-selective male fisheries may result in sperm limitation whereby the number of sperm is insufficient to fertilize all oöcytes produced by females. In eubrachyuran crabs, females have seminal receptacles for sperm storage which may reduce the risk of sperm limitation over their lifetime. In this study on the commercially exploited eubrachyuran Metacarcinus edwardsii, we evaluate the sperm limitation hypothesis by measuring female reproductive success in five Chilean populations subjected to low or high fishing intensity. The quantity and viability of sperm stored by females was measured in each season and population, and related to resulting brood fecundity. Females’ sperm reserve was larger when fishing intensity was low than when it was high—paralleling previously demonstrated differences in males’ sperm reserve—and especially in the season before oviposition. Sperm viability was in general high (92%) and independent of fishing intensity. Mean brood fecundity adjusted to constant female size was about 60% greater under low compared with high fishing intensity. Thus, in M. edwardsii, population reproductive output could be depressed by male-biased fishing in spite of female sperm storage capability.